Determinants of public opinion support for a full embargo on Russian energy in Germany - Bruno Castanho Silva; Jens Wäckerle; Christopher Wratil (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Western powers have discussed and implemented several policies in response to the full scale Russian invasion of Ukraine in February 2022. One such possible answer was an immediate embargo on all Russian energy exports to the EU. While seen as a strong measure against Russia's war effort, some EU governments were unenthusiastic, due to potential negative economic impacts on the short run, by pressuring prices for consumers and fueling inflation. Public opinion also seemed divided on the matter. We use a framing survey experiment in Germany (n = 3, 251) to test what factors influence support for an immediate embargo against Russian energy. Results indicate that out of seven possible frames tested, the only one that has an effect on embargo support is whether the rest of the German public is in favor or not. Results are in line with contemporary models of public opinion formation and legitimacy, and shed light on the conditions that may help framing other potentially costly issues to garner public support, such as measures to tackle climate change.
Keywords: D91; 330; public opinion; survey experiment; Russian energy embargo; foreign policy; Ukraine war